The effect of managerial intention and initiative on green supply chain management adoption in Indonesian manufacturing performance - Ilyas Masudin; Tri Wastono; Fien Zulfikarijah (Cogent Business & Management, 2018)
The objective of this study is to determine the influence of initiative and intention for an organization to adopt green supply chain management (GrSCM). The effects of GrSCM implication and trust inter-organization to organization performance are also determined in this study. In this article, quantitative research is done by collecting 91 purposive sampling data of Indonesian manufacture and descriptive and inter-correlation analysis using SPSS and smartPLS. The results of this study show that the initiative influences positively and significantly to the adoption of GrSCM application, while intention has no significant effects on GrSCM adoption. The application of GrSCM has a low significant relationship to the organization performance. Moreover, the initiative variable is not able to moderate GrSCM application; however, trust is able to moderate the influence of GrSCM adoption to organization performance.
Keywords: 650